Pemetaan Sistematis Dalam Topik Kajian Sustainable Development Goals (SDGs) Berdasarkan Analisis Bibliometrik - Ramadhani, Baity Jannati; Nugraheni, Nursiwi (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2024)
Sustainable Development Goals (SDGs) which is a sustainable agenda until 2030 with the aim of being able to improve the prosperity of the world community. The aim of this research is to determine publication trends, determine trends in terms in titles, and determine trends in terms used in abstracts of articles about SDGs using bibliometric analysis. The articles used were found with the help of Publish or Perish (PoP) with a database from Google Scholar. There were 389 articles out of 598 articles found from the Google Scholar database from 2021 to 2024 that were analyzed in this research. Selected articles are then managed using Mendeley software, after the database is managed, they are visualized using Vosviewer software. In this research, it was found that from 2021-2023 there was an increase in publications related to SDGs articles. The term that is often used in titles and abstracts is "SDGs".